2019
DOI: 10.1016/j.mayocpiqo.2018.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use in Fibromyalgia Is Associated With Cognitive Dysfunction

Abstract: Objective To evaluate the association between smoking and cognitive function in patients with fibromyalgia. Patients and Methods We surveyed 668 patients with fibromyalgia from May 1, 2012 through November 30, 2013 at a major tertiary referral center. Patients were categorized by smoking status. Primary outcome of interest was cognitive function (MASQ questionnaire), and secondary outcomes included fibromyalgia symptom severity (FIQ-R questionnaire), quality of life (SF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
(49 reference statements)
1
18
0
Order By: Relevance
“…Data on correlation analysis between Fibromyalgia severity scale (FSS) and 9 domains of FANTASTIC lifestyle checklist (FLC) stratified according to gender, year of study and division of study alcohol use in FM patients. Ge et al [28] found that to bacco smokers reported higher severity of FM and relat ed symptoms, while another study found that moderate alcohol consumption improved quality of life and symp tom severity of FM patients [29].…”
Section: Discussionmentioning
confidence: 97%
“…Data on correlation analysis between Fibromyalgia severity scale (FSS) and 9 domains of FANTASTIC lifestyle checklist (FLC) stratified according to gender, year of study and division of study alcohol use in FM patients. Ge et al [28] found that to bacco smokers reported higher severity of FM and relat ed symptoms, while another study found that moderate alcohol consumption improved quality of life and symp tom severity of FM patients [29].…”
Section: Discussionmentioning
confidence: 97%
“…This was a prospective questionnaire study consisting of 668 total patients with FM who were referred to the Fibromyalgia and Chronic Fatigue Clinic at a tertiary referral center and completed the Fibromyalgia Treatment Program from May 1, 2012, through November 30, 2013. 17 All patients had a confirmed diagnosis of FM in accordance with the 1990 or 2010 American College of Rheumatology criteria. 2 , 26 The initial cohort consisted of consecutive patients who completed baseline questionnaires before attending treatment sessions at the program.…”
Section: Methodsmentioning
confidence: 99%
“…However, limited studies have examined sex-based differences in the FM patient population, and findings to date are controversial and inconclusive. 17 , 18 Some studies report worse symptoms and clinical outcomes in men with FM, 19 , 20 some report worse outcomes in women with FM, 20 , 21 and some report no differences. 22 , 23 , 24 These discrepancies may be related to sociodemographic and geographical heterogeneity, 9 , 19 , 25 methodological flaws in observational studies not controlling for potential confounding factors, 24 and lack of use of validated instruments to evaluate outcome measures.…”
mentioning
confidence: 99%
“…Interestingly, there were no associations between history of smoking or history of psychiatric disorder with responder status after DRG implantation. Studies reveal that tobacco use may intensify pain response via a pathway of increased circulating pro‐inflammatory cytokines (29,30). Similarly, studies also reveal that psychiatric comorbidities, especially untreated psychiatric disorders that are not optimized preimplantation, predict poor response to neuromodulation (31,32).…”
Section: Discussionmentioning
confidence: 99%